Impacts of Different Internationalization Modes on the Global Competence of Chinese University Students - Xi Yang (杨希); Tingsong Li (李亭松) (ECNU Review of Education)
Purpose This study examines the impacts of two modes of internationalization on students’ global competence, namely, internationalization abroad and at home. This study divides global competence into five secondary dimensions to further explore the impacts of the different modes of internationalization on each dimension. Design/Approach/Methods This study uses a propensity score matching design to estimate the impacts of different modes of internationalization on university students’ global competence. Data were collected from high-level research universities in China. Findings Concerning experiences of internationalization abroad, overseas travel and visits were found to have no significant effect on university students’ global competence, whereas studying abroad significantly improved the latter. In terms of experiences of internationalization at home, engagement with international curricula and contact with foreigners had a significantly positive effect on university students’ global competence. Originality/Value The study results demonstrate that internationalization at home is an effective way to enhance students’ global competence and is of considerable theoretical and practical significance in the post-COVID-19 pandemic era.